The Role of Social Media in Educational Communication Management - Ohara, Muammar Revnu (PT. LITERASI SAINS NUSANTARA, 2023)
Social media has experienced rapid development and become an important part of people's daily lives. This phenomenon has also impacted the world of education, where educational institutions and students are increasingly using social media as a means of communicating and interacting. This research aims to dig deeper into how social media can be optimised to strengthen educational communication effectively while addressing the potential risks that arise. The current research type is qualitative. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. This study found that social media has a significant role in educational communication management. By facilitating information sharing, collaboration, active participation and professional development, social media has changed the way we interact and learn in this digital era. However, the use of social media also brings challenges related to invalid information, privacy, cyberbullying and online bullying.